Dendritic cell membrane-based DCsLipo@MnO2@siCTLA4@PD-1α nanomedicine for the treatment of Lynch syndrome-related colorectal cancer - Wenjin Zhong; Pengcheng Wang; Jintian Wang; Yuejia Zhu; Liquan Chen; Yilong Qian; Xiang Huang; Kai Ye (Materials Today Bio, 2025)
Background: The immune checkpoint inhibitor (ICI) PD-1α can effectively treat Lynch syndrome (LS)-associated colorectal cancer (CRC) (LS-CRC). In some cases, LS-CRC is not sensitive to ICIs. Dendritic cell (DC)-based hybrid membrane nanoparticles have great potential to upgrade the efficacy of ICIs, which can theoretically be applied to enhance the efficacy of ICIs in treating LS-CRC. Methods: MnO2 nanomaterials with si-CTLA4 were absorbed by coating mature DCs loaded with PD-1α and liposome hybrid membranes. The morphology and physicochemical properties of DCsLipo@MnO2@si-CTLA4@PD-1α were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), dynamic light scattering (DLS), fluorescence resonance energy transfer (FRET), and Fourier transform infrared spectroscopy (FTIR). The activation of DCs and T cells was assessed by utilizing the detection of cell surface markers by flow cytometry. The mRNA levels of CTLA4 in T cells were measured using the qPCR method. The biosafety of DCsLipo@MnO2@si-CTLA4@PD-1α was proved by hemolysis test in vitro, CCK-8 assay, and live/dead cell staining. In vitro T-cell uptake experiments proved that the nanomedicine can be effectively absorbed by T cells. Cell proliferation, apoptosis, and ELISA experiments demonstrated that nanomedicine facilitated T-cell proliferation, cytokine secretion, and cancer cytotoxicity. Finally, the anti-cancer effect and immune activation ability of the nanomedicine against LS-CRC were verified by a mouse allograft model. Results: The nanomedicine DCsLipo@MnO2@si-CTLA4@PD-1α created in this research exhibited good stability and uniform vesicle morphology. In vitro hemolysis test, CCK-8 assay, and live/dead staining experiments indicated that DCsLipo@MnO2@si-CTLA4@PD-1α had great biosafety. The nanoparticle loaded with si-CTLA4 effectively reduced the mRNA expression of CTLA4 in T cells. Meanwhile, the results of T cell flow analysis, cell proliferation, cytotoxicity, apoptosis, and ELISA experiments manifested that DCsLipo@MnO2@si-CTLA4@PD-1α effectively reinforced the proliferation and activation of T cells, and enhanced the cytotoxicity of T cells to cancer cells. The validation experiments based on the mouse allograft tumor model manifested that DCsLipo@MnO2@si-CTLA4@PD-1α boosted the infiltration of T cells into tumor tissues and suppressed the development of LS-CRC. Conclusion: DCsLipo@MnO2@si-CTLA4@PD-1α can facilitate T cell activation and synergistically enhance the efficacy of ICIs, exhibiting a great inhibitory effect on LS-CRC.